2009
DOI: 10.1161/circulationaha.108.791681
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Left Ventricular Early-Diastolic Lengthening Velocity

Abstract: Background-Peak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(73 citation statements)
references
References 31 publications
4
64
1
1
Order By: Relevance
“…These findings are best interpreted in light of recent data demonstrating that, in addition to early diastolic load (lengthening load), e' is determined not only by intrinsic myocardial relaxation, but also prominently influenced by restoring forces, particularly in the presence of normal LV function. 26 The amount of potential energy stored during contraction and released during relaxation is negatively related to end-systolic length and volume. The ability to reduce end-systolic length or volume, therefore, contributes to the active restoration of LV dimensions in early diastole and enhances the rate of relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are best interpreted in light of recent data demonstrating that, in addition to early diastolic load (lengthening load), e' is determined not only by intrinsic myocardial relaxation, but also prominently influenced by restoring forces, particularly in the presence of normal LV function. 26 The amount of potential energy stored during contraction and released during relaxation is negatively related to end-systolic length and volume. The ability to reduce end-systolic length or volume, therefore, contributes to the active restoration of LV dimensions in early diastole and enhances the rate of relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…52 Tan et al found that at rest, the extent and velocity of LV untwisting was impaired in HFpEF patients compared with controls, and further tended to be impaired during dynamic exercise, indicating that in addition to inadequate relaxation reserve, limitations in LV untwisting contribute. 14 Using nuclear scintigraphy, Phan et al observed that while peak diastolic filling rates were similar in HFpEF patients and controls at rest, the ability to enhance the time to peak filling was markedly attenuated in HFpEF.…”
Section: Pathophysiology Of Exercise Intolerance In Hfpefmentioning
confidence: 99%
“…Supporting such supposition, IVRT has been shown to improve with short-term training among sedentary subjects (20). Similarly, e 0 is primarily dependent on LV relaxation and reflects a combination of active, energy-consuming steps plus elastic recoil representing the cyclic restoration forces of the myocardium (21). E 0 has shown to be rather independent of LV preload (22,23), to decrease with diminished coronary blood flow, and to improve with exercise (20,24).…”
Section: Discussionmentioning
confidence: 95%